2022
DOI: 10.1200/jco.2022.40.16_suppl.4059
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant atezolizumab plus docetaxel/oxaliplatin/capecitabine in non-metastatic gastric and gastroesophageal junction adenocarcinoma: The PANDA trial.

Abstract: 4059 Background: Immune checkpoint blockade improves clinical outcomes for patients with gastric and gastro-esophageal junction (GEJ) cancers, but its efficacy and impact on the tumor microenvironment in non-metastatic, resectable disease remains largely unknown. Peri-operative FLOT, the current standard-of-care, leads to pathologic complete responses (pCR) and major pathologic responses (MPR) in 16% and 37% of patients, respectively. An important open question is whether PDL-1 blockade monotherapy can prime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Among the 33 included studies, there were seven randomized controlled trials (RCTs) ( 31 , 35 , 39 , 40 , 54 , 56 , 58 ) and 26 single-arm open-label cohort studies ( 27 , 28 , 30 , 32 34 , 36 38 , 41 53 , 55 , 57 , 59 , 60 ). The main neoadjuvant immunotherapy drugs used were avelumab, camrelizumab, pembrolizumab, sintilimab, tislelizumab, nivolumab, LP002, and durvalumab.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 33 included studies, there were seven randomized controlled trials (RCTs) ( 31 , 35 , 39 , 40 , 54 , 56 , 58 ) and 26 single-arm open-label cohort studies ( 27 , 28 , 30 , 32 34 , 36 38 , 41 53 , 55 , 57 , 59 , 60 ). The main neoadjuvant immunotherapy drugs used were avelumab, camrelizumab, pembrolizumab, sintilimab, tislelizumab, nivolumab, LP002, and durvalumab.…”
Section: Resultsmentioning
confidence: 99%
“…Toxicity data from this trial will be insightful to evaluate if the phenomena we describe in our case report are common. Additionally, the PANDA trial [5] combines capecitabine, oxaliplatin, and docetaxel with atezolizumab in a neoadjuvant fashion for resectable gastric and gastro-esophageal junction cancers. We eagerly await the toxicity data from this study as well.…”
Section: Discussionmentioning
confidence: 99%
“…The median follow-up of 29 months revealed a DFS rate of 75%. Two patients (10%) experienced grade 3 immune-related adverse events (IRAEs) ( Verschoor et al, 2022 ). Another single-arm, phase 2 trial (NCT03488667), also reported at ASCO 2022, showed 19% ypCR (tumor regression score, TRS = 0) and 92% pathological response (TRS ≤2) in 26 of 35 patients treated with neoadjuvant mFOLFOX plus pembrolizumab, with grade 3/4 toxicities reported in 21 patients ( Sun et al, 2022 ).…”
Section: Application Of Icis In the Perioperative Settingmentioning
confidence: 99%